Lipid Metabolic Disturbances in Severe Sepsis: Clinical Significance and New Methods of Correction - O. G. Malkova; I. N. Leiderman; A. L. Levit; S. P. Nitenko (Общая реаниматология)
Objective: to reveal the basic regularities in the development of lipid metabolic disturbances in severe sepsis and to evaluate the efficiency of parenteral use of new balanced lipid emulsions in this cohort of patients. Subjects and methods. A prospective study was conducted in 88 patients with severe sepsis of different etiologies in the intensive care unit (ICI), Sverdlovsk Regional Clinical Hospital One. Among the lipid metabolic parameters, serum cholesterol, triglycerides (TG), high-density lipoproteins, low-density lipoproteins, and atherogenicity index were measured. Out of the systemic inflammatory markers and the additional criteria for sepsis severity, the serum levels of C-reactive protein, nitric oxide, lactate, D-dimers, the anti-inflammatory cytokine IL-4 and the proinflammatory cytokine IL-8 were determined. Serum was taken on days 1, 3, 5, and 7 after admission to the ICI. The quantitative attributes were comparatively analyzed by the statistical program «Statistica 6.0». Results. The severity assessed by the APACHE II scale, the degree of multiple organ failures (MOF) evaluated by the SOFA scale, and lung lesion according to the MURREY scale were found to be closely related to the baseline serum TG levels in patients with severe sepsis. The findings suggest that patients with high TG levels have much higher resuscitative mortality rates. The clinical evaluation of the efficiency of the new method for correction of lipid metabolic disturbances in severe sepsis has indicated that the patients receiving balanced (omega-3 fatty acids-enriched) fat emulsions as 20% Lipoplus solution had lower APACHE II scores within the first 7 days of intensive therapy and significantly more positive SOFA MOF changes. Specific changes were revealed in the presence of systemic inflammatory markers, such as C-reactive protein, IL-8, and IL-4, which confirms that balanced lipid emulsions are able to affect the system of pro- and anti-inflammatory mediators. Conclusion. The baseline increased serum TG level may be regarded as an additional criterion for the severity of sepsis. The new-generation balanced fat emulsions used in the parenteral feeding program for patients with severe sepsis can reduce the severity of their condition and the manifestations of MOF and affect the system of pro- and anti-inflammatory mediators. Key words: severe sepsis, lipid metabolic disturbances, balanced lipid emulsions.